Determination of Efficient and Inefficient Stocks with the Capital Asset Price Model (CAPM) Method - I Wayan Sunarya (STIM LASHARAN JAYA MAKASSAR, 2020)
Stock selection by an investor needs to be done with a variety of existing analysis for example the application of the Capital Asset Price Model. In the Composite Stock Index known as LQ45 shares. LQ45 shares have a unique characteristic that is their shares are liquid, meaning their shares are favored by investors because the average has very good fundamentals. For this reason, in this study the selected stocks, LQ45 shares, are used to determine which shares are worth buying and which shares are not worth buying. Because the names of companies incorporated in LQ45 continue to change from year to year, in this study using a sample of LQ45 company data, amounting to 30 companies where the company was chosen because from 2017 to 2019, the company remains in the LQ45 stock group. For research data sources sourced from Yahoo Finance and take a variety of reading sources both through journals and online media. As for determining efficient and inefficient stocks lies in the value of the individual Expected Return or often abbreviated as [E (Ri)]. If the Individual Expected Return is greater than the value of the Individual Return (Ri) then the shares are in the efficient stock.